PELATIHAN DESAIN BRANDING DIGITAL UNTUK UMKM JAYAPURA MENGGUNAKAN CANVA - Rasna, Rasna; Jufri, Moh; Jusmawati, Jusmawati; Matdoan, Moh. Rahmat Irjii (Gapenas Publisher, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Jayapura play a crucial role in local economic growth and job creation but continue to face challenges in implementing effective branding designs as part of their marketing strategies. This study aims to explore the effectiveness of digital branding design training using the Canva application in enhancing the understanding and skills of MSME actors in Jayapura to create appealing and professional visual content. Using a descriptive quantitative approach, data were collected through surveys of training participants to measure their satisfaction levels and comprehension of the material provided. The study results indicate that most participants were very satisfied (45%) and satisfied (35%) with the training, while 10% were neutral, and only 10% were less satisfied or dissatisfied. The training positively impacted participants' abilities to design branding content relevant to the needs of the digital market, potentially increasing the appeal of Jayapura MSME products in an increasingly competitive market. The findings highlight the importance of continuous training for MSMEs to strengthen digital marketing strategies and support local economic growth and competitiveness. In conclusion, branding design training using Canva has proven to be an effective solution to help Jayapura MSMEs create attractive visual content, enhance branding skills, and support digital marketing efforts.